2019
DOI: 10.16888/interd.2018.35.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Tenacidad en estudiantes universitarios chilenos: Un estudio inicial de su estructura y red nomológica

Abstract: Traditionally, academic performance has been linked to intelligence and some other stu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
3
0
2
Order By: Relevance
“…Hua Ma et al (2019) identified that Grit is a variable mediating between happiness and social competence, i.e., people who are highly oriented toward happiness and determination also have certain social competencies. Cerda et al (2018) identified that women show greater perseverance (Grit) than men, and that, unlike findings from other studies (Duckworth et al, 2007;Duckworth and Quinn, 2009;Christensen and Knezek, 2014;Tyumeneva et al, 2014;Li, 2015) a high perseverance in effort goes necessarily hand in hand with a high consistency in interest. In other words, in order to perform well academically it is necessary to be highly persevering.…”
Section: Gritmentioning
confidence: 56%
See 1 more Smart Citation
“…Hua Ma et al (2019) identified that Grit is a variable mediating between happiness and social competence, i.e., people who are highly oriented toward happiness and determination also have certain social competencies. Cerda et al (2018) identified that women show greater perseverance (Grit) than men, and that, unlike findings from other studies (Duckworth et al, 2007;Duckworth and Quinn, 2009;Christensen and Knezek, 2014;Tyumeneva et al, 2014;Li, 2015) a high perseverance in effort goes necessarily hand in hand with a high consistency in interest. In other words, in order to perform well academically it is necessary to be highly persevering.…”
Section: Gritmentioning
confidence: 56%
“…Regarding sociodemographic variables, it is expected that women present higher levels of GRIT (Cerda et al, 2018;Daura et al, 2020), in the same way as first-generation students, since this group tends to develop strategies that allow academic continuity Berlanga Silvente et al, 2018, similarly, it is likely that younger students have lower levels of GRIT due to the characteristics of the stage in which they are; depending on the place of origin is expected to impact negatively on the levels of GRIT.…”
Section: Theory Of Basic Psychological Needsmentioning
confidence: 99%
“…Dentro de las consideraciones que sostienen quienes defienden la necesidad de agrupar los dos elementos en un constructo de segundo orden no solo se encuentran algunas centradas en los hallazgos consistentes de la correlación de la escala con el éxito en distintos escenarios (Cerda et al, 2018;Guerrero et al, 2016;Salles et al, 2017;Suzuki et al, 2015), sino que también se incluyen los estudios en los que se ha encontrado que la perseverancia en el esfuerzo, en ausencia de la consistencia en el interés, no es tan buen predictor de un mejor desempeño (Jachimowicz et al, 2018), o que dadas las características del escenario puede verse privilegiado uno de los atributos que componen el grit (Datu et al, 2016). En términos teóricos, bajo esta visión, los dos componentes del grit son necesarios para enfrentarse a tareas de alta complejidad en las que el avance implique no solo un proceso de superación de obstáculos a través del trabajo constante (perseverancia en el esfuerzo), sino un interés genuino por el objetivo deseado que promueva la motivación y un alto involucramiento durante el trabajo (consistencia en el interés).…”
Section: Discussionunclassified
“…In fact, other studies have reported a unidimensional structure for grit and/or used a total grit score compiled of PE and CI items (e.g., Areepattamannil & Khine, 2018; Baierschmidt, 2022; Cerda et al, 2018; Eskreis-Winkler et al, 2014; Gonzalez et al, 2020; He, Wang et al, 2021; Hossain et al, 2022; Ion et al 2017; Kannangara et al, 2018; Kooken et al, 2021; Lee & Sohn, 2017; Luthans et al, 2019; Muhammad et al, 2020; Sinclair, 2021; Usher et al, 2019). However, further studies have shown that grit is composed of two correlated factors.…”
Section: The Concept Of Gritmentioning
confidence: 99%